Iowa RBA, April 27, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Notes for the Iowa RBA for April 27, 1998. Highlights include Sprague's Pipit, Black-headed Gull, Yellow-crowned Night Heron and Black-legged Kittiwake. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed